2009
DOI: 10.1083/jcb.200906014
|View full text |Cite
|
Sign up to set email alerts
|

The glycosaminoglycan-binding domain of PRELP acts as a cell type–specific NF-κB inhibitor that impairs osteoclastogenesis

Abstract: The PRELP heparin sulfate–binding protein translocates to the nucleus, where it impairs NF-κB transcriptional activity, which in turn regulates bone homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 39 publications
2
64
1
Order By: Relevance
“…Adam8, which is a metalloproteinase induced by TNF acting as a sheddase for the TNF receptor I thereby limiting TNF activity,41 has the ability to limit leucocyte recruitment and inflammation 42 . Prelp , an extracellular matrix protein found in the synovial fluid of patients with RA, limits inflammation and complement activation-mediated cartilage attack and represses osteoclast differentiation 43 44 . Prg4 encodes for Lubricin, a protein essential for the maintenance of articular cartilage and a negative regulator of synovial hyperplasia, thereby protecting against arthritis-induced joint destruction 45–47 .…”
Section: Discussionmentioning
confidence: 99%
“…Adam8, which is a metalloproteinase induced by TNF acting as a sheddase for the TNF receptor I thereby limiting TNF activity,41 has the ability to limit leucocyte recruitment and inflammation 42 . Prelp , an extracellular matrix protein found in the synovial fluid of patients with RA, limits inflammation and complement activation-mediated cartilage attack and represses osteoclast differentiation 43 44 . Prg4 encodes for Lubricin, a protein essential for the maintenance of articular cartilage and a negative regulator of synovial hyperplasia, thereby protecting against arthritis-induced joint destruction 45–47 .…”
Section: Discussionmentioning
confidence: 99%
“…On a different note, prolargin (proline/arginine-rich end leucine-rich repeat protein) is a glycosaminoglycan and collagenbinding anchor protein that is abundantly expressed in cartilage, basement membranes and developing bone. 45 Previous studies have suggested that prolargin acts as a cell-type specific inhibitor of the NFκB pathway that impairs osteoclastogenesis. 45 In addition, increased NFκB activity has been shown to promote angiogenesis, invasion, metastasis, as well as chemoresistance in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…45 Previous studies have suggested that prolargin acts as a cell-type specific inhibitor of the NFκB pathway that impairs osteoclastogenesis. 45 In addition, increased NFκB activity has been shown to promote angiogenesis, invasion, metastasis, as well as chemoresistance in pancreatic cancer. 46 Thus, in VLTS, increased prolargin could potentially inhibit or diminish the NFκB signaling and thereby blocking tumorigenesis, invasion, angiogenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…G1251, minimum 99% pure; Sigma Chemical Co, St Louis, MO, USA) was dissolved in distilled water and prepared at a dose of 10 mg/kg, based on previous reports [19,20]. Estrogen (no.…”
Section: Glutamic Acid and E 2 Preparationmentioning
confidence: 99%